The Application of Video-Based Learning Method Using Playposit Application in Chinese Listening Skill by the Students of Chinese Education Study Program State University of Malang - Rajali, Muhamad; Widyatmoko, Tiksno; Sakti, Karina Fefi Laksana (Universitas Negeri Malang, 2023)
Chinese listening skills are often used when taking Chinese language proficiency tests. Students are often the main obstacle with more dominant learning modalities will affect the motivation and interest of students during learning. The video-based learning can balances the lack of student modalities in learning. The video-based learning method with Playposit application in Chinese listening skills and to find out students' responses to the use of the video-based learning method. This research uses a descriptive qualitative method with used observation sheet and questionnaire sheet. The results of the research on the application of video-based learning methods with the Playposit application in Chinese listening skills run well and smoothly based on the existing syllabus. The application of video-based learning methods gets a positive and diverse response, because video-based learning methods can help students listen to Chinese, are more interactive, and can make students more excited when learning.